Kepemimpinan Non-Muslim dalam Wacana Tafsir - Fatimah Askan (Al-Fanar: Jurnal Ilmu Al-Qur’an dan Tafsir, 2019)
This study uses the method of interpretation mauḍū’i. Through this method, the researcher traces and collects the verses of the Qur'an which refer to non-Muslim leadership, namely verses that contain the word awliyā’, then the verses are discussed and studied in depth to become a basis for answers the main problem being discussed. Historical studies have also been used, considering that this study deals with Jewish and Christian communities. This approach will be seen in the background study of the descent of the verse, the disclosure of the situation of Ahl al-Kitāb when the Qur'an was revealed and their interaction with the Muslims. From the historical side, it will be known the journey of their social interaction, then used as an objective assessment. Finally, in-depth analysis of the results of the search and collection of information from the verses of the Qur'an based on the two methods above, with the angle of analysis focused on non-Muslim leadership in three spheres; family scope, community scope and state scope.